Jesús Jiménez in Early 20th Century Postage Stamps - Brenes Tencio, Guillermo A. (2020)
Received: 01-24-2020 Approved: 03-27-2020 ABSTRACT  In Postage stamps are a type of image still very little explored in historical works in Costa Rica. This article studies the iconography of the Costa Rican president Jesús Jiménez Zamora (1823 - 1897) on three postage stamps that circulated in Costa Rica at the beginning of the 20th Century. With this purpose, we have started from the theoretical and methodological postulates proposed by the art historian Erwin Panofsky to face the imaginary analysis.